Honey is potentially effective in the treatment of atopic dermatitis: Clinical and mechanistic studies. Issue 2 (30th March 2017) - Alangari, Abdullah A.; Morris, Keith; Lwaleed, Bashir A.; Lau, Laurie; Jones, Ken; Cooper, Rose; Jenkins, Rowena
Abstract: Introduction: As manuka honey (MH) exhibits immunoregulatory and anti‐staphylococcal activities, we aimed to investigate if it could be effective in the treatment of atopic dermatitis (AD). Methods: Adult volunteers with bilateral AD lesions were asked to apply MH on one site overnight for seven consecutive days and leave the contralateral site untreated as possible. Three Item Severity score was used to evaluate the response. Skin swabs were obtained from both sites before and after treatment to investigate the presence of staphylococci and enterotoxin production. In addition, the ability of MH and its methanolic and hexane extracts to down regulate IL4‐induced CCL26 protein release from HaCaT cells was evaluated by enzyme linked immunosorbent assay. Also, the ability of MH to modulate calcium ionophore‐induced mast cell degranulation was assessed by enzyme immunoassay. Results: In 14 patients, AD lesions significantly improved post MH treatment versus pre‐treatment as compared to control lesions. No significant changes in the skin staphylococci were observed after day 7, irrespective of honey treatment. Consistent with the clinical observation, MH significantly down regulated IL4‐induced CCL26 release from HaCaT cells in a dose‐dependent manner. This effect was partially lost, though remained significant, when methanolic and hexane extracts of MH were utilized. In addition, mast cell degranulation was significantly inhibited following treatment with MH. Conclusions: MH is potentially effective in the treatment of AD lesions based on both clinical and cellular studies through different mechanisms. This needs to be confirmed by randomized and controlled clinical trials. Abstract : Topical treatment with manuka honey ameliorated the clinical sings in patients with atopic dermatitis. This effect could be related, at least partly, to down regulation of IL4‐induced CCL26 release from keratinocytes and inhibition of histamine release from mast cells.